PENGARUH PRODUK TERHADAP KEPUTUSAN PEMBELIAN INDOMIE GORENG DENGAN VARIABEL PROMOSI SEBAGAI MODERASI DI PT. INDOMARCO ADI PRIMA CABANG LUBUKLINGGAU - Supriyanto, Supriyanto; Effendi, Muhamad; Alfionita, Lara (Jurnal Media Ekonomi (JURMEK), 2020)
This research was conducted at PT. Indomarco Adi Prima Lubuklinggau Branch. The purpose of this study is to determine the effect of the product on purchasing decisions with promotion variables as moderation at PT. Indomarco Adi Prima Lubuklinggau Branch partially and simultaneously. The data collection technique used was a questionnaire. Respondents were consumers at PT. Indomarco Adi Prima Lubuklinggau Branch. The results of the research The effect of the product on the purchasing decision of Indomie Goreng, obtained tcountvalue of 3,797 and ttable is 0.1638 (ttable value n = 100) so it can be seen that if the criteria match tcount> tta ttable ble then Ho is rejected and Ha is accepted, which means that there is an influence. There is a significant difference between the product and the purchase decision of Fried Indomie, promotional moderation can strengthen the purchasing decision of Fried Indomie, the tcountis 5,261 and the ttable is 0.1638 (ttable value n = 100), then it can be seen that if the criteria are in accordance with tcount> ttable then Ho rejected and Ha accepted, which means that there is a significant influence between promotion and purchasing decisions Indomie Goreng, product influence, and promotion can strengthen Indomie Goreng purchasing decisions, That the effect of products on purchasing decisions is 12.8%. As well as the test results after the moderation variable, namely promotion can strengthen or increase purchasing decisions to 36.2%.